Gambaran Kejadian Miopia di SMAN 1 Cibadak Kabupaten Sukabumi - Ghiffari Muhammad Suriadi; Dicky Santosa; Tryando Bhatara (Bandung Conference Series: Medical Science, 2023)
Abstract. Myopia is a refractive disorder due to axial elongation of the eyeball, occurs when the image of a distant object is focused in front of the retina. According to the American Academy of Ophthalmology 2021, myopia is marked by blurring of distant objects and clearly visible objects near, according to WHO, in 2019 the prevalence of myopia reached 53% in Asia-Pacific and increased in high school students around 84.89%. This study aims to determine the incidence of myopia in students of SMAN 1 Cibadak, Sukabumi Regency. The sample selection technique for this study used probability sampling, with 92 research subjects. This study used an observational method with a cross-sectional approach. Data collection was carried out using an eye examination by a refractionist using an autorefractometer and Snellen chart. The results of this study showed that 65 students (70.4%) had myopia and 27 students (29.3) did not have myopia. The relatively high percentage of myopia associated with students at SMAN 1 Cibadak, Sukabumi Regency, can cause muscle tension, as well as activities that force the eyes to work in a monotonous manner for a long time and at close range, resulting in the eyes continuously accommodating. Keywords: high school students, myopia, refractive error Abstrak. Miopia merupakan kelainan refraksi akibat pemanjangan aksial bola mata, terjadi ketika bayangan benda jauh terfokus di depan retina. Menurut American Academy of Ophthalmology 2021 miopia ditandai dengan kaburnya objek yang jauh dan objek dekat terlihat dengan jelas, menurut WHO pada tahun 2019 prevalensi miopia mencapai 53% di Asia–pasifik dan meningkat pada siswa SMAN sekitar 84,89%. Penelitian ini bertujuan untuk mengetahui kejadian miopia pada siswa SMAN 1 Cibadak Kabupaten Sukabumi. Teknik pemilihan sampel penelitian ini menggunakan probability sampling, dengan subjek penelitian sebanyak 92 orang. Penelitian ini menggunakan metode observasional dengan pendekatan potong lintang. Pengambilan data dilakukan menggunakan pemeriksaan mata oleh refractionist menggunakan autorefractometer dan snellen chart. Hasil penelitian ini menunjukkan siswa yang mengalami miopia sebanyak 65 orang (70,4%) dan tidak miopia sebanyak 27 orang (29,3). Persentase terjadinya miopia berkaitan dengan siswa SMAN 1 Cibadak Kabupaten Sukabumi yang relatif tinggi dapat menyebabkan ketegangan otot, serta aktivitas memaksa mata untuk bekerja secara monoton dengan waktu yang lama dan jarak yang dekat sehingga berakibat pada mata yang terus menerus berakomodasi. Kata Kunci: kelainan refraksi, miopia, siswa SMA.